Highly sulfonated co-polyimides containing hydrophobic cross-linked networks as proton exchange membranes. Issue 29 (27th June 2016) - Yao, Hongyan; Song, Ningning; Shi, Kaixiang; Feng, Sinan; Zhu, Shiyang; Zhang, Yunhe; Guan, Shaowei
Abstract : The cross-linked highly sulfonated co-polyimides based on novel diamine monomer containing double hydrophobic cross-linkable tetrafluorostyrol side-groups showed improved enhanced dimensional stability and superior proton conductivity. Abstract : A novel diamine monomer bearing double hydrophobic cross-linkable tetrafluorostyrol side-groups has been successfully synthesized. Based on this monomer along with 4, 4′-diaminodiphenyl ether-2, 2′-disulfonic acid (ODADS) and 1, 4, 5, 8-naphthalenetetracarboxylic dianhydride (NTDA), a series of cross-linked highly sulfonated co-polyimide (CSPI y -6FATFVP x ) membranes with IEC values ranging from 2.07 to 2.41 meq g −1 were prepared via a high temperature poly-condensation, followed by a thermal cross-linking reaction. The SPI were synthesized by high temperature polymerization. The CSPI membranes were obtained from the SPI membrane by thermal crosslinking reation. The polymerization and crosslinking reation were not performed in one pot. The CSPI y -6FATFVP x membranes showed significantly excellent performance, especially the high proton conductivity (0.153–0.210 S cm −1 at 80 °C), low water uptake (54.1%–87.1% at 80 °C) and swelling ratio (15.5%–23.0% at 80 °C). Furthermore, the CSPI y -6FATFVP x membranes also exhibited outstanding thermal stability (5% weight loss when the temperature exceed 320 °C), excellent hydrolytic stability and mechanical properties. The results indicate that CSPI y -6FATFVP x are promising candidates as proton exchange membranes in fuel cell technology.